2015
DOI: 10.1021/ol5036497
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of a New Family of Dieckmann Cyclases Essential to Tetramic Acid and Pyridone-Based Natural Products Biosynthesis

Abstract: Bioinformatic analyses indicate that TrdC, SlgL, LipX2, KirHI, and FacHI belong to a group of highly homologous proteins involved in biosynthesis of actinomycete-derived tirandamycin B, streptolydigin, α-lipomycin, kirromycin, and factumycin, respectively. However, assignment of their biosynthetic roles has remained elusive. Gene inactivation and complementation, in vitro biochemical assays with synthetic analogues, point mutations, and phylogenetic tree analyses reveal that these proteins represent a new fami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
62
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(64 citation statements)
references
References 36 publications
0
62
0
2
Order By: Relevance
“…SCSIO1666 involved in tirandamycin biosynthetic pathway [14]. TrdC and its analogues SlgC, KirHI have been determined as Dieckmann cyclases, and they catalyze the formation of tetramic acid or pyridone moiety [21]. Bioinformatics analyses revealed that NcmC also possesses the characteristic catalytic traid Cys-Asp-His (Additional file 1: Figure S4).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…SCSIO1666 involved in tirandamycin biosynthetic pathway [14]. TrdC and its analogues SlgC, KirHI have been determined as Dieckmann cyclases, and they catalyze the formation of tetramic acid or pyridone moiety [21]. Bioinformatics analyses revealed that NcmC also possesses the characteristic catalytic traid Cys-Asp-His (Additional file 1: Figure S4).…”
Section: Resultsmentioning
confidence: 99%
“…The core structure of nocamycin is bicyclic ketal unit and tetramic acid moiety. To date, tetramic acid structure has been identified in numerous natural products and four phylogenetically different family enzymes have been characterized to catalyze the tetramic acid formation through Dieckmann cyclisation reaction [21, 4750]. In previous report, TrdC and its homologous protein SlgL have been characterized as Dieckmann cyclases to catalyze the formation of tetramic acid moiety in tirandamycin and streptolydigin biosynthetic pathway, respectively [21].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Compound 19 was subjected to acryloylation giving 28 in a high yield. Following the removal of the silyl group under mild acidic conditions, the free benzylic −OH group was then acylated using three different N-alloc protected amino acids giving the key precursor (29) to study the 15-membered ring formation by a ring closing metathesis stitching approach. As in the previous study, this reaction also worked-well, and in all the three cases, macrocyclic ring was obtained (see 30).…”
Section: Acs Combinatorial Sciencementioning
confidence: 99%